IMPLEMENTATION OF SCHOOL RELIGIOUS CULTURE IN THE FORMATION OF ELEMENTARY SCHOOL STUDENTS' MORALS: A STUDY AT AL-MUNAWWAR ISLAMIC ELEMENTARY SCHOOL, MANDAILING NATAL - Ria Rafita Supriani; Nurizki Mustamirrun; Amalia Zahra; Reski Wahyuni Hasibuan; Tuti Alawiyah Lubis; Liza Hafni; Wilda Rohani (LPPM Univ. Ibn Khaldun Bogor, 2026)
This study aims to analyze the implementation of school religious culture in shaping student morals at Al-Munawwar Integrated Islamic Elementary School in Mandailing Natal. This study used a qualitative approach with a descriptive approach. The research subjects included the principal, homeroom teachers, and students. Data collection techniques included observation, interviews, and documentation. Data analysis was conducted through data reduction, data presentation, and conclusion drawing, using source and technique triangulation to ensure data validity. The results indicate that the implementation of school religious culture is carried out through several activities, namely gate duty, routine religious activities, the habit of congregational prayer, and extracurricular activities. Gate duty plays a role in fostering politeness, respect for teachers, and discipline in students. Routine religious activities accustom students to practicing religious values in their daily lives. The habit of congregational prayer fosters discipline, responsibility, and etiquette in worship. Meanwhile, extracurricular activities serve as a means of strengthening moral values through direct practice, such as cooperation, responsibility, and compliance with rules. The conclusion of this study indicates that the planned and consistent implementation of a school religious culture can shape students' morals gradually and sustainably. School religious culture serves as an effective strategy in character education to shape students with noble morals and religious attitudes.